1993
DOI: 10.1152/ajpcell.1993.264.6.c1480
|View full text |Cite
|
Sign up to set email alerts
|

Distinct regulation of Na+ reabsorption and Cl- secretion by arginine vasopressin in the amphibian cell line A6

Abstract: The neurohypophysial peptide arginine vasopressin (AVP) increases Na+ absorption across A6 epithelia. In addition to the positive natriferic response, AVP increases net basolateral to apical Cl- flux. The time course of activation of electrogenic ion transport in A6 epithelia was examined by measuring transepithelial short-circuit current (ISC). Basolateral application of AVP (0.1 U/ml) or forskolin (10 microM) affects ISC in a biphasic manner. Shortly after addition of AVP, an early (transient) phase is obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
34
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 3 publications
12
34
0
Order By: Relevance
“…The biphasic time course of the I sc response to cAMP (Fig. 2) was consistent with previous studies in MDCK cells (43,54) and in A6 cells (4,8,29,44,58) that showed a rapid increase in anion secretion followed by a more gradual increase in Na ϩ absorption. The secretory anion current, represented by NS-I sc , was partially inhibited by 200 M glibenclamide (Figs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The biphasic time course of the I sc response to cAMP (Fig. 2) was consistent with previous studies in MDCK cells (43,54) and in A6 cells (4,8,29,44,58) that showed a rapid increase in anion secretion followed by a more gradual increase in Na ϩ absorption. The secretory anion current, represented by NS-I sc , was partially inhibited by 200 M glibenclamide (Figs.…”
Section: Discussionsupporting
confidence: 90%
“…The FLAG epitope allows the number of ENaC subunits residing in the apical membrane of the transfected MDCK cells to be quantified by the surface binding of 125 I-labeled anti-FLAG antibodies. Our initial studies with intact FL-MDCK monolayers in DMEM medium showed they had a high shortcircuit current (I sc ) and that cAMP treatment produced a rapid transient peak within 5 min followed by a broad peak that decayed over 20 min (43), as also described in A6 and M-1 cultures (8,29,34,44). The biphasic response to cAMP in all of these epithelia has been attributed to rapid Cl Ϫ secretion by CFTR activation followed by a slower cAMP-dependent activation of ENaC that is blunted by the inhibitory effect of CFTR.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…There is thus excellent agreement between the observed and predicted responses, and so the changes in G Cl Ϫ and G Na ϩ that we now report can explain the well-documented effects of isoprenaline upon these cells (23,30,(36)(37)(38). Moreover, in A6 cells, a Na ϩ -absorbing cell line derived from the amphibian kidney, cAMP-dependent agonists have been reported to elicit a biphasic response similar to that described above (7). This pattern of response may thus be a generalized feature of salt-absorbing epithelia.…”
Section: Discussionsupporting
confidence: 85%
“…Grown on permeable supports, they acquire polarity and express highly selective sodium channels (Kleyman et al 1989;Hamilton & Benos, 1990;Benos et al 1995). In addition, amiloride-sensitive Na¤ channels, cAMP-induced Na¤ channels (Verrey, 1994), highly conductive Cl¦ channels (Marunaka & Eaton, 1990) and non-selective cation channels (Hamilton & Benos, 1990) have been demonstrated in the same cells, together with the effect of factors like vasopressin Chalfont et al 1993;Smith et al 1995), aldosterone (Kemendy et al 1992;Willis et al 1992), insulin (Marunaka et al 1992;Record et al 1996) and cAMP (Hamilton & Eaton, 1991;Nakahari & Marunaka, 1995) on these channels. AÜ cells can be used as experimental analogues of frog skin with the advantage that they can be easily patched, while Cacoµ cells are, for similar reasons, equally convenient analogues of the mammalian large intestine.…”
mentioning
confidence: 99%